PROSPERITY AS REFLECTED IN FITZGERALD’S THE GREAT GATSBY - Tini Mogea (Jurnal Pendidikan dan Sastra Inggris, 2023)
This study aims to shed light on the prosperous era that occurred in America during the 1920s, as depicted in F. Scott Fitzgerald's The Great Gatsby. In conducting this research, the writer uses a qualitative method in which the data are in the form of words and the writer is the key instrument. The sources are taken from the work itself and other relevant books supporting the analysis. The writer employs a mimetic approach to data analysis, which holds that literary work is a reflection and imitation of aspects of the universe. As a result of remaining neutral during World War I and the occurrence of migration, America can now concentrate on economic mobilization. Prosperity is marked by the rise of consumerism, business fortune, and residence, but it also has a negative impact on the American people in terms of the rise of a new way of life and the decline of morality, such as a proclivity for free life, alcoholism, and free sex.